2018
DOI: 10.20533/ijtie.2047.0533.2018.0147
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting WebQuests to Develop Intercultural Communication Competence

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…However, the resources are typically information-focused which directs students to simply compare and contrast the similarities and differences between their own and the target cultures in a traditional way that is insufficient for the complexity of language and culture learning. Educators found that this type of traditional approach runs the risk of oversimplifying the richness and variety of a culture by reducing it to a few salient principles (Stockwell, 2018). Although language teachers have incorporated more culture in their lessons, the major concern is finding effective ways to integrate culture and language to prepare learners to engage and collaborate effectively in a global society by discovering appropriate ways to interact with people from other cultures.…”
mentioning
confidence: 99%
“…However, the resources are typically information-focused which directs students to simply compare and contrast the similarities and differences between their own and the target cultures in a traditional way that is insufficient for the complexity of language and culture learning. Educators found that this type of traditional approach runs the risk of oversimplifying the richness and variety of a culture by reducing it to a few salient principles (Stockwell, 2018). Although language teachers have incorporated more culture in their lessons, the major concern is finding effective ways to integrate culture and language to prepare learners to engage and collaborate effectively in a global society by discovering appropriate ways to interact with people from other cultures.…”
mentioning
confidence: 99%